2018
DOI: 10.1038/s41413-018-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine and endocrine actions of bone—the functions of secretory proteins from osteoblasts, osteocytes, and osteoclasts

Abstract: The skeleton is a dynamic organ that is constantly remodeled. Proteins secreted from bone cells, namely osteoblasts, osteocytes, and osteoclasts exert regulation on osteoblastogenesis, osteclastogenesis, and angiogenesis in a paracrine manner. Osteoblasts secrete a range of different molecules including RANKL/OPG, M-CSF, SEMA3A, WNT5A, and WNT16 that regulate osteoclastogenesis. Osteoblasts also produce VEGFA that stimulates osteoblastogenesis and angiogenesis. Osteocytes produce sclerostin (SOST) that inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
284
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(314 citation statements)
references
References 159 publications
4
284
0
6
Order By: Relevance
“…These results were in line with in vivo evidence and could suggest that the absence of DPP3 altered the crosstalk between the OC and the OB lineage: on one hand, it increased Dpp3 KO OC precursors’ responsiveness to OB‐derived molecular cues; on the other, it reduced OB activity. Therefore, we evaluated the expression of coupling factors, namely RANKL, OPG, Ephb4 , Wnt5a , and Lrp5 for the OB side, Bmp6 , Efnb2 , Wnt10b , Sema4d , and Ror2 for the OC side . We found that KO OC/KO OB, KO OC/WT OB, and WT OC/WT OB co‐cultures produced a similar amount of RANKL, which was higher than that in WT OC/KO OB co‐cultures (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…These results were in line with in vivo evidence and could suggest that the absence of DPP3 altered the crosstalk between the OC and the OB lineage: on one hand, it increased Dpp3 KO OC precursors’ responsiveness to OB‐derived molecular cues; on the other, it reduced OB activity. Therefore, we evaluated the expression of coupling factors, namely RANKL, OPG, Ephb4 , Wnt5a , and Lrp5 for the OB side, Bmp6 , Efnb2 , Wnt10b , Sema4d , and Ror2 for the OC side . We found that KO OC/KO OB, KO OC/WT OB, and WT OC/WT OB co‐cultures produced a similar amount of RANKL, which was higher than that in WT OC/KO OB co‐cultures (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Osteoblasts are responsible for bone matrix secretion and mineralization, and they tightly regulate osteoclast activation and differentiation (Nakamichi et al, ). During bone resorption induced by inflammation, the receptor activator of nuclear factor‐κB ligand (RANKL), which is from osteoblasts and marrow‐derived stromal cells, promotes osteoclastic precursors differentiate into mature osteoclasts by binding to its cognate receptor, RANK (Han, You, Xing, Zhang, & Zou, ; Horowitz, Xi, Wilson, & Kacena, ; Steeve, Marc, Sandrine, Dominique, & Yannick, ). Osteoprotegerin (OPG), largely secreted by osteoblast lineage cells, functions as a soluble decoy receptor for RANKL that inhibits the RANKL/RANK link and osteoclastogenesis (Simonet et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bone remodeling is a constant process necessary to maintain the integrity and biological functions of the skeleton. Essentially, bone remodeling involves removal of old or damaged bone by osteoclasts and subsequent new bone formation by osteoblasts . Furthermore, osteocytes embedded in the bone matrix, as the terminally differentiated phenotype of osteoblasts, are previously thought to be less significant in bone remodeling, but recently emerged as a regulator of bone homeostasis .…”
Section: Imaging Of Cellsmentioning
confidence: 99%
“…As for cell‐cell interactions, previous studies have revealed both paracrine and endocrine actions of osteoblasts and osteoclasts to influence each other . However, evidence of direct cell‐cell contact between osteoclasts and osteoblasts is rarely provided, since they occupy discrete territories in the steady state.…”
Section: Imaging Of Cellsmentioning
confidence: 99%